The Xenophobic Attacks on African Immigrants - Emmanuel Michael Massay; Novri Susan (Journal of Contemporary Sociological Issues, 2023)
Since the country's xenophobic violence in 2008, the 2019 xenophobic assaults are a new reminder of South Africa's anti-immigrant prejudice. Xenophobia threatens refugees, asylum seekers, economic migrants, and other designated geographical "outsiders," including internal migrants and minority ethnic groups. This study will provide an overview of xenophobia in South Africa and insights into its occurrence by examining the conflict profile, including the background, actors, causes, and the present dynamic of the conflict. In this qualitative study, the exploratory analysis concentrates on a thorough examination of available secondary data. Issues regarding economic tensions, hatred, and hate speech surfaced as a reality of conflict. The Generalized Deterrence Theory (GDT) will support this research and explain why certain people behave criminally, oddly, or anti-socially. Thus, this study argues that measuring economic improvement and improving land policy is a potential treatment for xenophobia. Until the problems of unemployment and poverty are resolved, xenophobia will decrease proportionately. Nevertheless, political games, which tend to take the form of hate speech, have proven to impact disputes and should be avoided. Keywords: Xenophobia, Conflict, hate speech, economic tension, South Africa